2013
DOI: 10.1103/physrevlett.111.165702
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Ferroelectric Domains in Nanostructures Under Electron Beams

Abstract: Freestanding BaTiO3 nanodots exhibit domain structures characterized by distinct quadrants of ferroelastic 90° domains in transmission electron microscopy (TEM) observations. These differ significantly from flux-closure domain patterns in the same systems imaged by piezoresponse force microscopy. Based upon a series of phase field simulations of BaTiO3 nanodots, we suggest that the TEM patterns result from a radial electric field arising from electron beam charging of the nanodot. For sufficiently large chargi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 40 publications
7
43
0
Order By: Relevance
“…In the present work we extend this analysis to relate to quantitative measurements of domain wall velocities [21][22][23][24][25][26][27] and effective masses for domain walls.…”
Section: Richtmyer-meshkov Instabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work we extend this analysis to relate to quantitative measurements of domain wall velocities [21][22][23][24][25][26][27] and effective masses for domain walls.…”
Section: Richtmyer-meshkov Instabilitiesmentioning
confidence: 99%
“…We can use the creep velocity v = 1 nms -1 from Tybell, Paruch and Triscone; 23 see also more recently Ng, Ahluwalia et al [24][25][26] and Scott and Kumar. 25 The effective mass for the wall is ca.…”
Section: Open-channel Viscous Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…These have been studied in some detail previously. [13,[32][33][34] In particular, we know that these arrays can be moved via an electron beam in an electron microscope, [35] and that they exhibit creep. [36,37] It is often found that ferroelectric nano-domains are nested inside larger ferroelastic domains such that the polarization (and hence depolarization energy) averages mesoscopically to zero; but the opposite case, of ferroelastic domains nested inside larger ferroelectric domains seems rare.…”
mentioning
confidence: 99%
“…100 ferroelectric nano-domains (see Fig.9, bottom diagram). The fact that the ferroelectric domains can be reoriented within a larger ferroelastic superdomain by application of electric field has been demonstrated by electron beam irradiation [34,35] with faceting and de-faceting observed.…”
mentioning
confidence: 99%